Research on the effect of Tai Chi's development in the southeast of Hubei on the promotion of rural revitalization - Feng, Shuolei; Ma, Zhiyu (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: General Secretary Xi Jinping emphasized in the report of the 19th National Congress of the Communist Party of China that in the implementation of the rural revitalization strategy, agriculture, rural areas, and farmers are fundamental issues related to the economy. Improving people’s livelihood and enhancing the supply of rural public sports services is the rural revitalization strategy. An important part of. The purpose of implementing the rural revitalization strategy is to enrich the material, spiritual and cultural life of the rural people, so as to meet the growing needs of the rural people for a better life, and to solve the contradiction between demand, unbalanced development and insufficient development. In his report to the 19th National Congress of the Communist Party of China, General Secretary Xi Jinping emphasized more clearly that without a high degree of cultural self-confidence and cultural prosperity, there would be no great rejuvenation of the Chinese nation. Tai Chi has a profound traditional cultural heritage in our country, and its movements are slow and gentle. At the same time, the exercise does not require high training venues and sports equipment. Therefore, there are many practitioners of Tai Chi at home and abroad. Tai Chi can help exercisers improve their physical functions, assist in the treatment of chronic diseases, and improve their quality of life. In the construction of a healthy China, the national and local governments must support and promote Tai Chi events that already have a broad mass base, and they must attach great importance to Tai Chi events. This article selects the poor counties in southeastern Hubei province to conduct field investigation and questionnaire survey to explore the development status of Tai Chi in this area and its role in promoting the development of national fitness in rural revitalization. Methods: literature method, expert consultation method, questionnaire survey method, and field investigation method. First, search the keywords "Tai Chi", "National Fitness" and "Rural Revitalization" through HowNet, and look up literature and books. A large number of related works have been searched in various databases such as CNKI, and related literature materials have been inquired. To understand the possible elements of promoting rural revitalization and development, as well as the current situation of Tai Chi activities, so as to provide a theoretical basis for this research. Secondly, before conducting the survey, I consulted experts on traditional ethnic sports in Wuhan Institute of Physical Education, officials of the local sports bureau, and the president and secretary-general of the Tai Chi Association of the region. A preliminary understanding of the development of Tai Chi in the area will help to form a more scientific research framework. At the same time, the questionnaire survey question content of this research has been determined. The field survey selected Tuanfeng County in Hubei Province as a representative. Tuanfeng County is located in the southeast of Hubei, the southern foot of the Dabie Mountains, and the north bank of the middle reaches of the Yangtze River. It covers an area of 838 square kilometers and has a total population of 380,000. There are 296 administrative villages (communities) in 8 towns and 2 townships. At the same time, a certain number of people were randomly selected from different groups to conduct a questionnaire survey. A total of 120 questionnaires were distributed and 113 were returned, of which 110 were valid questionnaires. Results: 1. The local government of Tuanfeng County and the Sports Bureau attach great importance to supporting and promoting traditional national sports such as Tai Chi. Tai Chi is an important component of the traditional cultural carrier of the Chinese nation. It combines the essence of multi-disciplinary knowledge in the traditional Chinese culture for thousands of years. It is very popular among local people, especially middle-aged and elderly people. Paying attention to the health of middle-aged and elderly people is the livelihood of all countries in the world, and the health protection of middle-aged and elderly people is also an important manifestation of social harmony and national progress in our country. 2. Compared with other sports, the development of Tai Chi in the impoverished counties in southeastern Hubei is more active. The number of local Tai Chi activities developed and participated in far exceeds that of other sports. It can be seen from the ever-growing Tai Chi training team and the increasingly frequent Tai Chi activities. The number of registered members of the local Tai Chi Association is 279, of which around 120 people often participate in activities. The main participants in Tai Chi are retired elderly people over 60 years old. The quality of rural sports, cultural and recreational activities and fitness and sports guidance services is improving day by day, and they are all making full preparations for providing rich sports material and spiritual and cultural life for the township people. 3. Long-term practice of Tai Chi can enhance the activity of the human body, prolong the lifespan of cells, and enhance the immunity of the human body. At the same time, the exercise of this exercise can also effectively relieve psychological pressure, reduce the level of anxiety, improve the stress ability of participants, and promote the coordinated development of interpersonal relationships. Conclusion: 1. The local government attaches great importance to the development of Tai Chi. Under the current situation that the national fitness project and the national fitness path are not fully covered, Tai Chi is conducive to the development of national fitness in the area, and the health of the middle-aged and elderly is conducive to the stable and harmonious development of society, Is conducive to accelerating the development of rural revitalization. 2. Tai Chi is developing vigorously in Tuanfeng County, and at the same time it plays a very important role in national fitness. Its fitness effect is different from basketball, swimming, football, track and field and other sports. Tai Chi is mainly aerobic. To be able to exercise, Tai Chi does not require high physical fitness on the venue, and it is suitable for promotion in towns and villages in southeastern Hubei. 3. Tai Chi exercise is a low-intensity exercise. A proper amount of Tai Chi exercise can effectively improve the immune function of the participants. Long-term Tai Chi exercises can also promote the physical and mental development of the exercised people. Tuanfeng County Tai Chi has a large number of participants and a wide audience, but its level of development is still low. The people generally hope that the government will increase financial support and strengthen professional guidance in the organization and development of the sport.